BUILDING GLOBAL FOOD SECURITY THROUGH ORGANIC FARMING PRACTICES: A LITERATURE REVIEW - Loso Judijanto (Adisam Publisher, 2025)
Organic farming is identified as one of the sustainable approaches with great potential to improve global food security. Through practices that maintain soil quality, enhance biodiversity, and reduce negative impacts on the environment, organic farming offers environmentally friendly solutions that can strengthen the global food system. This literature review explores the benefits and challenges faced in the widespread adoption of organic agriculture. It was found that, although organic agriculture contributes positively to sustainability and nutritional quality, lower production compared to conventional methods and various obstacles such as access to markets and limited knowledge are major obstacles. Therefore, policy support, economic incentives, technological innovation, and education are needed to maximise the potential of organic agriculture. Collaboration between stakeholders is essential in facing challenges and promoting organic agricultural practices as an integral solution for food security in the future.